Clinical detection and categorization of uncommon and concomitant mutations involving BRAF. Issue 1 (December 2015) - Zheng, Gang; Tseng, Li-Hui; Chen, Guoli; Haley, Lisa; Illei, Peter; Gocke, Christopher; Eshleman, James; Lin, Ming-Tseh
Abstract Background Selective BRAF inhibitors, vemurafenib and dabrafenib, and the MEK inhibitor, trametinib, have been approved for treatment of metastatic melanomas with aBRAF p.V600E mutation. The clinical significance of non-codon 600 mutations remains unclear, in part, due to variation of kinase activity for different mutants. Methods In this study, we categorizedBRAF mutations according to the reported mutant kinase activity. A total of 1027 lung cancer, colorectal cancer or melanoma specimens were submitted for clinical mutation detection by next generation sequencing. Results Non-codon 600 mutations were observed in 37 % ofBRAF -mutated tumors. Of allBRAF mutants, 75 % were kinase-activated, 15 % kinase-impaired and 10 % kinase-unknown. The most common kinase-impaired mutant involves codon 594, specifically, p.D594G (c.1781A > G) and p.D594N (c.1780G > A). Lung cancers showed significantly higher incidences of kinase-impaired or kinase-unknown mutants. Kinase-impairedBRAF mutants showed a significant association with concomitant activatingKRAS orNRAS mutations, but notPIK3CA mutations, supporting the reported interaction of these mutations. Conclusions BRAF mutants with impaired or unknown kinase activity as well as concomitant kinase-impairedBRAF mutations andRAS mutations were detected in lung cancers, colorectal cancers and melanomas. Different therapeutic strategies based on theBRAF mutant kinase activity and the concomitant mutations may be worthwhile.